2022
DOI: 10.1038/s41564-022-01072-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities form rich extracellular metabolomes that foster metabolic interactions and promote drug tolerance

Abstract: Microbial communities are composed of cells of varying metabolic capacity, and regularly include auxotrophs that lack essential metabolic pathways. Through analysis of auxotrophs for amino acid biosynthesis pathways in microbiome data derived from >12,000 natural microbial communities obtained as part of the Earth Microbiome Project (EMP), and study of auxotrophic–prototrophic interactions in self-establishing metabolically cooperating yeast communities (SeMeCos), we reveal a metabolically imprinted mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 82 publications
0
79
0
Order By: Relevance
“…It has so far been debated if unicellular organisms would profit from a longer lifespan and if they have been selected for longevity 83 . Our study does not address this question directly, but it reveals an interesting new possibility, in the light that a vast majority of natural microbial communities contain auxotrophs 38,74 . Evolution could increase longevity by selecting for populations of cells that metabolically interact in a way that they generate a protective exometabolome.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has so far been debated if unicellular organisms would profit from a longer lifespan and if they have been selected for longevity 83 . Our study does not address this question directly, but it reveals an interesting new possibility, in the light that a vast majority of natural microbial communities contain auxotrophs 38,74 . Evolution could increase longevity by selecting for populations of cells that metabolically interact in a way that they generate a protective exometabolome.…”
Section: Discussionmentioning
confidence: 94%
“…The generation and culture of SeMeCos was performed as previously described 38 . The pH, pL, pU and pM plasmid used to generate a SeMeCo strain in the BY4741 background are described in Table S3.…”
Section: Semeco Generation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…S1E). (Yu et al, 2022) This suggested that metabolite sharing is more effective at overcoming the loss of MET17, at least when compared to the other three other auxotrophies. In order to understand the role that metabolite sharing plays in overcoming the loss of MET17 in the SeMeCo system, we recorded the metabolic profiles of SeMeCos by LC-SRM and compared these against the metabolic profiles of prototrophic communities.…”
Section: The Conditional Nature Of Organosulfur Auxotrophy In Met17∆ ...mentioning
confidence: 99%
“…We have previously generated proteomes from sorted auxotrophs and prototrophs from SeMeCo cultures (Yu et al, 2022). To distinguish auxotrophs from prototrophs, we used cosegregation of cyan fluorescent protein (CFP) with the relevant auxotrophic marker expressed from the same plasmid (PRIDE project: PXD031160).…”
Section: The Conditional Nature Of Organosulfur Auxotrophy In Met17∆ ...mentioning
confidence: 99%